Boom‐Baby CEOs, Career Experience, and Risk Taking: A Natural Experiment Using Chinese CEOs' Growth Paths1. (23rd January 2018) - Hao, Ying; Wang, Shaofei; Chou, Robin K.; Ko, Kuan‐Cheng
Abstract: China's economy represents a unique experimental environment, in that it has undergone a successful transformation from a planned to a more open system. Leveraging this natural experimental setting, this study examines the impacts of CEOs' formative experiences on their risk‐taking behavior. Two events likely constitute formative experiences for CEOs: economic reforms that commenced in 1978 and their prior career experiences. In turn, CEOs' risk tolerance attitudes likely reflect the influences of these significant events. The results show that CEOs who experienced economic reforms in their early adult life exhibit higher risk‐taking likelihood and greater risk tolerance than those who grew up during the planned economy era. Furthermore, firm performance achieved by CEOs' risk taking is significantly better when CEOs originally started working in and then remained within business sectors.